Respuesta a la aplicación de dosis de roca fosfórica con humus de lombriz en el cultivo de tomate (Lycopersicum esculentum. mill) var. “Río Grande”, en un suelo ácido del fundo Aucaloma de la UNSM – Lamas - Amacifuén Flores, Juan Carlos (2012)
This research paper entitled "Response to the application of phosphate rock with doses of vermicompost in tomato (Lycopersicum esculentum. Mill) var. "Big River", in an acid soil of the farm Aucaloma UNSM - Lamas ", were to: assess the responses phenological, morphological and yield of tomato (Lycopersicum esculentum. Mill, var." Rio Grande ") to application of 05 doses of phosphate rock and humus in an acid soil of the farm Aucaloma district of San Roque de Cumbaza, Lamas province and San Martín region and assess the effect of phosphate rock in the incidence and severity of diseases presented in tomato (Lycopersicum esculentum. Mill var. "Rio Grande") in acid soils and on yield. The experimental design was randomized complete block (RCBD) with 7 treatments and 4 replications, treatments were: control, worm manure (4 t/ha), rock phosphate (0.5 t/ha) + (4 t/ha) worm compost, rock phosphate (1 t/ha) + (4 t/ha) worm compost, rock phosphate (1.5 t/ha) + (4 t/ha) worm compost, rock phosphate (2 t/ha) + (4 t/ha) worm compost, rock phosphate (2.5 t/ha) + (4 t/ha) Humus. The variables evaluated were: plant height, number of vegetative branches, number of flower clusters, number of flowers per plant, number of fruits per plant, fruit weight, yield in kg ha-1, economic analysis of the treatments, incidence and severity of pests and diseases. The most significant findings were: The highest plant height was achieved with treatments T2 (4 t/ha/humus) and T6 (2 t/ha/RF + 4 t/ha/humus) to 58.57 cm and 56, 66 cm, the effect of vermicompost mainly longitudinal growth that facilitated thereof. T5 treatment (1.5 t/ha/RF + 4 t/ha/humus) won the largest number of flowers per plant with 16.95 flowers/plant, more number of fruits per plant and heavier fruits 16.85 of fruits and 688.50 716.75 g/plant, thanks to balanced supply of phosphorus. Furthermore economic returns was 78/100 cents for each new sun reversed. Likewise, the performance obtained T5 was 19.11 t/ha, resembling the T4 with 18.36 t/ha treatments being presented better answers